Transmittal Policy : The Exchange of Documents Between the Fund and Other Organizations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
history of exchanging documents with other international organizations and currency unions. The practice of exchanging documents with individual organizations dates back to the 1940s, mostly conducted through bilateral arrangements with other international organizations and currency unions. In 1990, the Fund introduced a framework (the 'Transmittal Policy') for the transmittal of certain Board documents (relating to Article IV consultations, use of Fund resources and, later, technical assistance). The Transmittal Policy has served the institution well, but some gaps have emerged over time. Many of the current bilateral document sharing arrangements were adopted in response to individual organizations' requests, thus document sharing arrangements have not always been applied uniformly to similar organizations or kept pace with the mandates and needs of the organizations. This has resulted in similar organizations having uneven access to Fund documents. Moreover, the Fund's Transparency Policy has also evolved and prompt publication of most Board documents is now the norm. The proposals set forth in this paper seek to ensure a consolidated, evenhanded approach to the transmittal of Fund documents to international organizations and currency unions. In particular, this paper proposes several changes that would allow international organizations and currency unions to receive a wider range of documents. This paper also presents a proposal responding to requests by Executive Directors of European Union (EU) countries to expand access to documents and information prior to Board consideration for the European Commission (EC). Staff proposes that access be granted uniformly to the EC and other executive bodies of currency unions that have executive decision-making power over the common economic and monetary policies of currency unions. There is also an interest in more expanded sharing of Fund documents with regional financing arrangements (RFAs) in view of their importance in the Global Financial Safety Net. However, given the unique structure of RFAs and the need to develop a policy framework suited for the needs of both the Fund and RFAs, a proposal for such sharing will be put forward in a separate paper for consideration by the Board.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet